2007
DOI: 10.1002/jat.1281
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde accumulation in rat mammary tissue after an acute treatment with alcohol

Abstract: Previous studies reported the presence in rat mammary tissue of a cytosolic xanthine oxidoreductase pathway for the metabolism of alcohol to acetaldehyde and hydroxyl radicals and to the microsomal biotransformation of ethanol to acetaldehyde. It was also reported that after chronic ethanol drinking stressful oxidative conditions can be observed. The present work reports that even after single doses of ethanol, given at three different levels (6.3 g kg(-1); 3.8 g kg(-1) or 0.6 g kg(-1) p.o.), acetaldehyde accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Alcohol dehydrogenase (ADH) metabolizes EtOH into acetaldehyde, its primary carcinogenic metabolite (Secretan et al, 2009) in breast cancer cells where it accumulates within mammary tissues following alcohol consumption (Castro et al, 2008). Using human cell, animal cell, and in vitro models, acetaldehyde was observed to form DNA adducts (Rintala et al, 2000;Vaca et al, 1998).…”
Section: The Role Of Ethanol Metabolismmentioning
confidence: 98%
“…Alcohol dehydrogenase (ADH) metabolizes EtOH into acetaldehyde, its primary carcinogenic metabolite (Secretan et al, 2009) in breast cancer cells where it accumulates within mammary tissues following alcohol consumption (Castro et al, 2008). Using human cell, animal cell, and in vitro models, acetaldehyde was observed to form DNA adducts (Rintala et al, 2000;Vaca et al, 1998).…”
Section: The Role Of Ethanol Metabolismmentioning
confidence: 98%
“…In rats, acetalde-hyde accumulates in mammary tissue for prolonged periods of time after a single oral dose of ethanol and finally reaches a level considerably higher than in blood [115,116]. This is primarily due to increasing production of acetaldehyde in mammary tissue, the limited ability to detoxify acetaldehyde in mammary tissue and acetaldehyde produced elsewhere and delivered to mammary tissue via blood [108].…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Tissues in vivo are simultaneously exposed to ethanol and acetaldehyde due to ubiquitous distribution of alcohol dehydrogenase (ADH)3, CYP2E14 and catalase56, all known to metabolize ethanol into acetaldehyde. Mounting evidence indicates that ethanol metabolism by ADH into acetaldehyde plays a crucial role in alcoholic tissue injury in many organs78910111213. Studies reported so far have evaluated the effect of either ethanol or acetaldehyde on tissue functions, including the epithelial barrier function.…”
mentioning
confidence: 99%